Kinetic DTI of the cervical spine: diffusivity changes in healthy subjects - Kuhn, Félix P.; Feydy, Antoine; Launay, Nathalie; Lefevre-Colau, Marie-Martine; Poiraudeau, Serge; Laporte, Sébastien; Maier, Marc A.; Lindberg, Pavel (Neuroradiology, 2016)
Introduction The study aims to assess the influence of neck extension on water diffusivity within the cervical spinal cord. Methods IRB approved the study in 22 healthy volunteers. All subjects underwent anatomical MR and diffusion tensor imaging (DTI) at 1.5 T. The cervical cord was imaged in neutral (standard) position and extension. Segmental vertebral rotations were analyzed on sagittal T2-weighted images using the SpineView® software. Spinal cord diffusivity was measured in cross-sectional regions of interests at multiple levels (C1–C5). Results As a result of non-adapted coil geometry for spinal extension, 10 subjects had to be excluded. Image quality of the remaining 12 subjects was good without any deteriorating artifacts. Quantitative measurements of vertebral rotation angles and diffusion parameters showed good intra-rater reliability (ICC = 0.84–0.99). DTI during neck extension revealed significantly decreased fractional anisotropy (FA) and increased radial diffusivity (RD) at the C3 level and increased apparent diffusion coefficients (ADC) at the C3 and C4 levels ( p < 0.01 Bonferroni corrected). The C3/C4 level corresponded to the maximal absolute change in segmental vertebral rotation between the two positions. The increase in RD correlated positively with the degree of global extension, i.e., the summed vertebral rotation angle between C1 and C5 ( R = 0.77, p = 0.006). Conclusion Our preliminary results suggest that DTI can quantify changes in water diffusivity during cervical spine extension. The maximal differences in segmental vertebral rotation corresponded to the levels with significant changes in diffusivity (C3/C4). Consequently, kinetic DTI measurements may open new perspectives in the assessment of neural tissue under biomechanical constraints.